Model-Based Approaches to the Internet of Things - Hirmer, Pascal (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book gives an overview of existing models that cover the whole lifecycle of an IoT application, ranging from its design, implementation, deployment, operation, and monitoring to its final termination and retirement. Models provide abstraction and can help IoT application developers into creating more robust, secure, and reliable applications. Furthermore, adaptation of applications can be eased by using these models, leading to an increased dynamic of the developed IoT applications. In the book, research of the last years in the area of model based approaches to the Internet of Things is described and these approaches are incorporated into the lifecycle of IoT applications. Finally, use cases from different domains are introduced that show how these models could be applied in real-world applications.
Introduction -- Foundations -- Scenarios and Challenges -- Life Cycle of an IoT Application -- Model Based Approaches to the Internet of Things -- Discussion -- Conclusion and Summary.
Keywords: Software engineering; Internet of things; Cloud Computing; Software Engineering; Internet of Things; Cloud Computing